Plan estratégico para mejorar la gestión administrativa de la Cooperativa de Ahorro y Crédito Sinchi Runa ltda. del cantón Saquisilí, provincia de Cotopaxi en el periodo 2014 - 2017 - Iza Toapanta, Trancito Liliana (2015)
This research had as an objective to elaborate the strategy plan in order to improve the administration management in “Sinchi Runa Ltda.” Credit and Saving Cooperative, through the formulation of corporate philosophy, we established the strategy objectives and development of competitive strategies, the method that was used in the research was of descriptive character and the skills that were applied for the information recollection were, observation, interview and the survey through this we an internal and external analysis….